The evolution of a hybrid regime in Chavista Venezuela: between democracy and authoritarianism - Gombata, Marsílea (2020)
This dissertation aims to provide a better understanding of the political system in Venezuela during the chavismo years. By analyzing the erosion of the Chavista democratic project over the years, the main idea is to figure out whether chavismo was democratic and became an authoritarian regime, or whether it had always been a hybrid one - with features from democracy and authoritarianism from the beginning. To adjudicate between these two premises, I have analyzed the transformation processes of the Venezuelan political system in the last 21 years. The main findings are that the process of erosion of Venezuelan democracy since 1999 has occurred in part due to clashes between government and opposition - as with the 2002 coup and the 2007 Constituent Assembly referendum, for instance - in which democratic aspects of the regime were weakened and authoritarian features became more prominent over the years. Because of this, I conclude that chavismo has always been a hybrid regime. However, in contrast to a transformation process from democracy to authoritarianism, in Venezuela I have seen a process in which authoritarian features have been strengthened and democratic ones have been diminished. I also argue that with Chávez, the Venezuelan political system was a hybrid one with a democratic leaning. With Maduro, it has changed, and Venezuela now has a hybrid political system on the authoritarian side. The future of the regime, however, is uncertain.